2011
DOI: 10.1364/oe.19.025866
|View full text |Cite
|
Sign up to set email alerts
|

Strained germanium thin film membrane on silicon substrate for optoelectronics

Abstract: This work presents a novel method to introduce a sustainable biaxial tensile strain larger than 1% in a thin Ge membrane using a stressor layer integrated on a Si substrate. Raman spectroscopy confirms 1.13% strain and photoluminescence shows a direct band gap reduction of 100meV with enhanced light emission efficiency. Simulation results predict that a combination of 1.1% strain and heavy n(+) doping reduces the required injected carrier density for population inversion by over a factor of 60. We also present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 30 publications
3
93
0
Order By: Relevance
“…The strain variation across the membrane is sufficiently small that optical device performance would not be affected by strain-induced variation in the Ge bandgap across the entire membrane. 23 Coupled with the smoother surface and absence of misfit dislocation network, compared to the bulk material, we have shown that these tensile strained Ge membranes are excellent strain tuning platforms for optical applications. …”
Section: à3mentioning
confidence: 73%
See 1 more Smart Citation
“…The strain variation across the membrane is sufficiently small that optical device performance would not be affected by strain-induced variation in the Ge bandgap across the entire membrane. 23 Coupled with the smoother surface and absence of misfit dislocation network, compared to the bulk material, we have shown that these tensile strained Ge membranes are excellent strain tuning platforms for optical applications. …”
Section: à3mentioning
confidence: 73%
“…However, under sufficient tensile strain Ge can becoming a direct band gap material and so a tensile-strained Ge crystalline membrane could be a useful platform for a Ge light source, or other Ge-based optical devices. Recently, thin (<1 lm) freestanding Ge membranes 22,23 and various other suspended structures 13 have been fabricated through relatively simple processing. Nam et al 22 and Kurdi et al is not homogenous in its properties then other effects apparently observed on further straining may be a composite from a spectrum of different strain values and in actuality luminescence may be shaper, rather than broader, in response to strain.…”
mentioning
confidence: 99%
“…Initial research effort was put into creating thin-film Ge membranes suspended in air, and then transferring external strain via various methods, such as water pressure, gas pressure, and stressor layer [17,[22][23][24][25][26][27][28]. More recently, a few researchers have presented novel structures to induce large tensile strain in Ge, in which a small residual tensile strain in Ge can be greatly amplified due to geometric effects [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…12 Germanium membranes of thickness 1.6 lm have previously been fabricated by Nam et al 13 which were tensile strained to reduce the direct band gap for more efficient light emission. Devices for optoelectronic detection were fabricated on the membranes to demonstrate this effect, and later they demonstrated roomtemperature electroluminescence opening the possibility for Ge lasers.…”
Section: Introductionmentioning
confidence: 99%